LOCAL MEANS OF THERMAL DIAGNOSTIC CONTROL OF ELECTRICAL EQUIPMENT FUNCTIONALITY: Array - Yesaulov, S.; Kovalenko, A.; Babichevа, O.; Khuruzha, D. (Municipal economy of cities (Technical science), 2021)
Attention is drawn to the lack in many municipal transport models of off-line testing engineering tools of on-board parameters and assessment of electromechanical equipment in real time. These development restraints are caused by stagnation of engineering decisions that can be eliminated with the help of the unlimited possibilities of modern microelectronics. It has been considered an example of thermal control of electrical equipment during its operations. The popularity of the thermal method of equipment control is confirmed by its application not only in transport, but also in electromechanical devices. It has been considered methods of using several thermal transducers for collecting data and forming matrices characterizing a certain class of breakdowns. The most important matrix is ​​the initial one, which refers to the serviceable equipment at the beginning of equipment operations. Due to increased reliability of data, it is advisable to develop effective methods for selective selection of initial values. The paper drew attention to the possibility of solving such problems by software with the implementation of comparison methods, sorting options, etc. The peculiarity of algorithms development for such auxiliary operations is due to the possibility of creating data arrays for the practical identification of possible failures, both in individual parts of the equipment and in the set of components as a whole. It has been presented the results of the binary representation of intermediate and final information messages, which greatly simplify the implementation of diagnostic examination tools. Modeling in the Matlab environment confirmed acceptability of proposed engineering decisions adapted for their implementation by means of processors with RISC-architecture. Despite the fact that binary methods of breakdowns technical appraisal will always differ much more inaccuracy than those made on the basis of direct measurements, proposed autonomous local binary experts in onboard versions of their implementation in transport are less labor-intensive, do not require maintenance, are economical and may turn out to be good helpers to prevent possible equipment failures when operating vehicles on passenger service lines.